Intracellular nutrient storage during ice algal spring blooms in the Canadian high Arctic - C.J. Mundy; Eva Leu; Karley Campbell; Virginie Galindo; Maurice Levasseur; Michel Poulin; Jean-Éric Tremblay; Michel Gosselin (iScience, 2025)
Summary: Nutrient availability influences maximum biomass, speciation, cellular composition, and overall phenology of Arctic spring ice algal blooms. However, how ice algae obtain nutrients from their environment is not well understood. Previously documented positive relationships between sea ice nutrient concentrations and algal biomass implied that ice algae maintain an intracellular nutrient pool. Here, we provide direct evidence that sea ice diatoms store intracellular nitrate + nitrite and silicic acid well above that available in their ambient environment. Differential retention of intracellular pools released during standard melt processing techniques led to an increase in the apparent dissolved N:Si ratio measured in ice melt samples that likely influenced interpretations of Si-limitation in some previous studies. It is hypothesized that the ability of ice algae to store intracellular nutrient reserves represents a beneficial adaptation for ice algae to extend blooms under a periodic tidal-pulsed flux of nutrients to the ice bottom environment.